Expandindo a sala de aula: recursos tecnológicos ubíquos em processos colaborativos de ensino e aprendizagem - Gomes, Celso Augusto dos Santos (2011)
This work is guided by two shows evidence. The first is the emergence of cyberspace beyond the fixed desktop and what has occurred with the growing use of mobile devices such as tablets and smartphones, connected to the World Wide Web. The second evidence is the urgent need for educational praxis that can follow, in context, pluralistic communication ecology which is configured with the growing pervasiveness of technology that tends to present today. ), this paper presents research results through the literature and case analysis from the perspective of complex thinking. At the convergence of the thinking of authors like Edgar Morin, Lucia Santaella, André Lemos, Jean Piaget, Ivan Illich, Ulisses Araújo, Ricardo Pátaro among others, this dissertation sought directions for the planning, implementation and evaluation of educational activities that make use of the ubiquity communication technology resources. These activities allow the dialogue between the intra and extracurricular situations in collaborative contexts of construction and reconstruction of knowledge from the educational perspective of assumptions epistemological socioconstructivist, contextualized with the growing presence in the physical environment of cyberspace from the perspective of complex thinking